Estimativa da evapotranspiração real por meio de imagens do satélite landsat 8 - Silva, Bruno Bonemberger da (2014)
The estimate evapotranspiration is a key factor in sustainable water management in irrigated agriculture, the actual crop water requirement established objectively, without generating waste of energy and water by excessive irrigation, and, on the other side, without compromising the agricultural production by its deficit. In this sense, the study aimed to estimate the daily actual evapotranspiration (-Etr) to local and regional scale, using Landsat 8 images (- OLI / TIRS), and additional data collected from a weather station, applying the Surface Energy Balance Algorithm for Land algorithm (- SEBAL). The study area is located in the west of Paraná, in Salto do Lontra County, consisting of irrigated agricultural area, native vegetation and urban area. It was used orbit image / site 223/78 in Julian days 336 2013 and 19, 35, 131 and 195 in 2014. The daily ETr was estimated from the latent heat flux density (LE), obtained from the equation residue of the energy balance. The algorithm consists of several steps which include radiometric calibration, the reflectance calculation, the surface albedo, vegetation index (NDVI, SAVI, and leaf area index - LAI), and emissivity, which are obtained from data from the sensor reflective bands orbital, with the surface temperature estimated from the thermal band. The results showed that the algorithm estimated the components of the energy balance, with higher values than the results generally obtained from previous studies. Concerning to the estimated Etr, there was good agreement between estimates obtained by SEBAL and by the Penman Monteith FAO 56 model, validating the algorithm. The errors between the models were less than or equal to 1.00 mm day-1, results similar to those found in the literature.